Social protection, entrepreneurship and labour market activation - Michael MacLennan; Fábio Veras Soares; Carolina Robino (International Policy Centre for Inclusive Growth (IPC-IG), 2015)
Despite significant development gains in recent decades, developing countries still face considerable challenges in regards to the fight against poverty and hunger. Redistributive cash transfer programmes have emerged as vital for the pursuit of poverty reduction and eradication; however, critics have expressed concerns that such social grants could lead to dependency among beneficiaries, dissuade them from seeking work, or reinforce traditional gender roles. Authors contributing to this issue of Policy in Focus address these concerns head-on, by exploring both the positive and unintended negative impacts of cash transfers on households and communities, while bringing to light some of the persisting challenges related to the limits of cash transfers. This issue introduces readers to research-based evidence on diverse social protection programmes in various countries, as well as current debates on how best to improve social grants. The contributing authors demonstrate the importance of evaluation results to better inform programme reforms and design changes to ensure that beneficiaries exit poverty and reduce their chances of slipping back into it. Furthermore, the following articles also help identify successful and potential synergies between various programmes and initiatives, highlighting the power of cash transfers in combination with other programmes, in order to better inform policymakers and further the discussions about how best to grow in a more inclusive and sustainable manner. [...]
Keywords: 330; Social Protection; Entrepreneurship; Labour Market Activation